Unresectable Carcinoma Pancreas: A Study on Clinical Presentations, Laboratory Investigations and Imagings (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: At the time of diagnosis most of pancreatic cancer is in the advanced stage and curative resection becomes impossible. These inoperable diseases are labeled as uresectable carcinonma pancreas. Accurate and early assessment is essential for such patients to gain a better outcome.Objective: This study was carried out to evaluate clinical presentations, laboratory investigations, histopathology and imaging modalities used to diagnose and label pancreatic carcinoma as unresectable.Methods: This retrospective study was carried out from July 2004 to June 2006 in BIRDEM Hospital, Dhaka. After careful scrutiny of clinical presentation, laboratory imaging studies, tissue diagnosis, tumor markers and operative findings it was seen that 50 patients (sample size n = 50) were labeled as unresectable carcinoma pancreas. Male patients were 28 (n1 = 28) and female patients were 22 (n2 = 22). Chi-square (?2) test was applied and P value